Implementation of ICT-Based Teacher Administration System to Improve Teaching and Learning Activities - Andri Sutrisno; Muhammad Masruri Dalail; Izzat Amini (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2023)
One of the  educational goals  is the  implementation  of  teaching and  learning activities well in the boarding school environment. For this reason, it is necessary to carry out Information and Communication  Technology  (ICT)  based  documentation  so  that  it  can  be  enjoyed  together  and evaluated the performance of the teachers' service at TMI Al-Amien Prenduan. As for the existence of an ICT-based teacher administration system, it is actually a form of consensus between the caregiver and several teachers in improving the skills of teachers in the field of technology and online-based information. Given the increasingly massive technological developments in contemporary times. This research  is  included  in  qualitative  field  research  with  a  case  study  research  approach.  The  data collection techniques used are observation, interviews and documentation. While the  data analysis techniques used are data reduction, data presentation and data verification. This research results in the implementation of an ICT-based teacher administration system in the field of curriculum, teacher self- development and examination results of the students. While the positive impact of SAG-TMI is the cooperation between the principal and the teachers for the achievement of good teaching and learning process activities so that it can be seen directly by the guardians of the students' academic achievements in the pesantren through ICT-based SAG-TMI.